REKONSTRUKSI PEMIKIRAN FILSAFAT PENDIDIKAN ISLAM - Ina Herlinawati; Ahmad Hidayat; Aat Royhatudin (Staisman Press, 2025)
This study aims to reconstruct Islamic educational philosophy in order to produce a philosophical framework that is more relevant and adaptive to the challenges of modernity. The research design uses a Qualitative-Philosophical approach and Library Research, critically analyzing primary and secondary sources related to Islamic educational philosophy and reconstructionism theory. The results of the analysis show that there is a fundamental philosophical gap in contemporary Islamic education, especially in the aspects of epistemology (the dichotomy of religious and general knowledge) and axiology (the imbalance of purpose orientation between the world and the hereafter). This gap hinders the formation of perfect human beings who are able to optimally carry out the function of khilafah in the global era. In response, this study proposes a New Philosophical Model: Transformational Tawhid Epistemology. This reconstruction model is based on three pillars: (1) Ontological Reconstruction, affirming humans as Integral Tawhid Beings who are balanced in their functions as 'abd and khalifah; (2) Epistemological Reconstruction, eliminating dichotomy by making Tawhid the vertical axis of integration of all sciences; and (3) Axiological Reconstruction, establishing the goal of education as the Formation of Prophetic Humans oriented towards Social Transformation and public problem solving (muslih). The conclusion of this study emphasizes the urgency of shifting the paradigm from education that merely passes on traditions to education that is proactive, critical, and oriented towards social change (prophetic). This reconstruction model is expected to become the theoretical basis for the development of a more comprehensive, integrative, and futuristic Islamic education curriculum and policy.